Download presentation

1
**Solve an equation with an extraneous solution**

EXAMPLE 5 Solve an equation with an extraneous solution Solve x + 1 = 7x x + 1 = 7x + 15 Write original equation. (x + 1)2 = ( 7x + 15)2 Square each side. x2 + 2x + 1 = 7x + 15 Expand left side and simplify right side. x2 – 5x – 14 = 0 Write in standard form. (x – 7)(x + 2) = 0 Factor. x – 7 = 0 or x + 2 = 0 Zero-product property x = 7 or x = –2 Solve for x.

2
EXAMPLE 5 Solve an equation with an extraneous solution CHECK 1 Check x = 7 in the original equation. Check x = –2 in the x + 1 = 7x + 15 x + 1 = 7x + 15 7 + 1 ? = 7(7) + 15 –2 + 1 ? = 7(–2) + 15 8 = 64 ? –1 = 1 ? 8 = 8 = 1 / –1 The only solution is 7. (The apparent solution 22 is extraneous.) ANSWER

3
**Solve an equation with two radicals**

EXAMPLE 6 Solve an equation with two radicals x = 3 – x . Solve SOLUTION METHOD 1 Solve using algebra. x = 3 – x Write original equation. x 2 = 3 – x 2 Square each side. x x = 3 – x Expand left side and simplify right side. 2 x + 2 = – 2x Isolate radical expression.

4
**Solve an equation with two radicals**

EXAMPLE 6 Solve an equation with two radicals x + 2 = –x Divide each side by 2. x + 2 2 = ( –x)2 Square each side again. x + 2 = x2 Simplify. = x2 – x – 2 Write in standard form. = (x – 2)(x + 1) Factor. x – 2 = 0 or x + 1 = 0 Zero-product property. x = 2 or x = –1 Solve for x.

5
EXAMPLE 6 Solve an equation with two radicals Check x = 2 in the original equation. Check x = – 1 in the original equation. x = 3 – x x = 3 – x = 3 – 2 ? – = 3 – (–1) ? 4 +1 = 1 ? 1 +1 = 4 ? = –1 / 3 2 = 2 The only solution is 1. (The apparent solution 2 is extraneous.) ANSWER

6
EXAMPLE 6 Solve an equation with two radicals METHOD 2 Use: a graph to solve the equation. Use a graphing calculator to graph y1 = and y2 = Then find the intersection points of the two graphs by using the intersect feature. You will find that the only point of intersection is (21, 2). Therefore, 21 is the only solution of the equation x + 2 3 – x x =

7
**( ) GUIDED PRACTICE for Examples 5 and 6**

Solve the equation. Check for extraneous solutions 11. x – 1 2 = 4 1 x x – 1 2 = 4 1 x Write original equation. (x )2 1 2 ( ) 4 x = Square each side. x2 –x = x 1 4 Expand left side and simplify right side. x2 – x = 0 1 4 5 4x2 – 5x + 1 = 0 Write in standard form. (4x – 1)(x – 1) = 0 Factor.

8
**The only solution is 1 (the apparent solution 1/4 is extraneous)**

GUIDED PRACTICE for Examples 5 and 6 4x – 1 = 0 or x – 1 = 0 Zero-product property. x = 1 4 or x = 1 Solve for x. Check x = 1 in the original equation. Check x = in the 1 4 x – 2 1 4 x = x – 2 1 4 x = = ? 1 – x 1 4 1 2 4 1 2 – = ? x 2 1 = ? 4 – 4 1 = ? 16 2 1 = 4 1 – = The only solution is 1 (the apparent solution 1/4 is extraneous)

9
**( ) GUIDED PRACTICE for Examples 5 and 6**

Solve the equation. Check for extraneous solutions 12. 10x + 9 = x + 3 10x + 9 = x + 3 Write original equation. 10x + 9 = ? (x + 3)2 ( ) 2 Square each side. Expand right side and simplify left side. 10x + 9 = x2 + 6x +9 x2 – 4x = 0 Write in standard form. x (x – 4) = 0 Factor. (x – 4) = 0 or x = 0 Zero-product property. x = 4 or x = 0 Solve for x.

10
**GUIDED PRACTICE for Examples 5 and 6 Check x = 4 in the**

original equation. Check x = 0 in the 10x + 9 = x + 3 10x + 9 = x + 3 10x = ? 10x = ? = ? = ? 3 = 3 = ? 7 = 7 The solution are 4 and 0.

11
**( x + 7 ) ( ) GUIDED PRACTICE for Examples 5 and 6**

Solve the equation. Check for extraneous solutions 13. 2x + 5 x + 7 = 2x + 5 x + 7 = Write original equation. ( ) 2 2x + 5 ( x + 7 ) = Square each side. 2x + 5 = x + 7 Simplify both the sides. x – 2 = 0 Simplify. x = 2 Simplify.

12
**Check x = 2 in the original equation**

GUIDED PRACTICE for Examples 5 and 6 Check x = 2 in the original equation 2x + 5 x + 7 = 2 + 7 = ? 9 = ? 3 = 3 The solution is 2.

13
**( ) ( ) GUIDED PRACTICE for Examples 5 and 6**

Solve the equation. Check for extraneous solutions x + 6 – 2 x – 2 14. = Solve x + 6 –2 x – 2 = Write original equation. ( ) 2 x + 6 –2 ( ) 2 x – 2 = Square each side. x + 6 – 4 x = x – 2 Simplify each side. – x + 6 = – 12 x + 6 = 3

14
**( ) GUIDED PRACTICE for Examples 5 and 6 x + 6 = 3 2 x + 6 = 32**

Divide each side by –4. ( ) 2 x + 6 = 32 Square each side. x + 6 = 9 Simplify. x = 3 Simplify.

15
**Check x = 3 in the original equation**

GUIDED PRACTICE for Examples 5 and 6 Check x = 3 in the original equation x + 6 – 2 = x – 2 – – 2 = ? 9 – = ? 1 = 1

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google